Incidencia de los acuerdos de paz en la economía colombiana durante el periodo 2012-2017 (2019)
This articule has the intention to investigate about the benefits of the peace process with the FARC on the colombian economy. In order to carry out this project, we have made a descriptive research and a non-experimental transversal design, for to determine the peace process’s impact in variables like: foreign direct investment, imports, exports, GDP and turism. The main result found out on this articule is the growth evinced on principals economic variables during the period 2012-2017 right after the beginning of the peace process, which is gonna bring along more employment, more opportunities and more equity